Introduction: Sites of reckoning special issue. (June 2023) - Burnet, Jennie; Zaretsky, Natasha
This introduction explores the theories and themes presented in the articles of this special issue. It considers embodiment, temporality, and coherence as they relate to healing and survival at memory sites dedicated to reckoning with difficult or contentious pasts. This special issue deliberately decenters traditional approaches in memory studies by carving out spaces for the Global South and by considering activist–scholar or activist–artist–scholar interventions. This special issue includes articles on Argentina, Cambodia, Nicaragua, Namibia, Rwanda, Russia, South Africa, South Korea, and the United States.